OPTIMALISASI PERAN GURU DALAM PROSES TRANSFORMASI PENGETAHUAN DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN - Muhammad Rusydi Rasyid (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
The traditional blackboard is really very much like a computer screen. It can be used to explain ideas graphically, with text and numbers, and can be used by the students like an interactive interface in a computer. The use of films, videotapes, audiotapes, records, and even performance can enhance the learning process in the classroom. The technique of using media requires creativity and planning. What media are available? How many of them should be used? Do media have psychological effect to students? What is the proper role for teaching with media? Media in the classroom are appropriate for triggering ideas, making difficult subjects more under-standable, and for holding attention on important ideas. They should lead students to remember ideas by becoming more involved with them.